A new species of Elaphidion Audinet-Serville, 1834, from Antigua and comparison with E. excelsum Gahan, 1895, from Guadeloupe (Coleoptera: Cerambycidae: Elaphidiini) - Vlasak, Josef (Zootaxa, 2019)
A new species of Elaphidion, E. antiguensis sp. nov. is described from Antigua (West Indies). The host plants and larval biology of E. antiguensis are described and compared to those of E. excelsum, Gahan.